2002
DOI: 10.1021/ma011205a
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Kinetics of Surface Migration of Surface Modifying Macromolecules in Membrane Preparation

Abstract: Surface modifying macromolecules (SMM) were synthesized and blended into the casting solution of poly(ether sulfone). The solution was cast to films with thickness of 0.12 and 0.24 mm. The cast films were placed in an oven with forced air circulation for periods of 3, 5, 7, and 2000 min to remove the solvent, before being immersed into water at 4°C for gelation. The membranes so prepared were further dried and subjected to contact angle measurement and XPS (X-ray photoelectron spectroscopy) analysis. It was fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
60
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(64 citation statements)
references
References 16 publications
3
60
0
1
Order By: Relevance
“…The additive concentration in membrane matrix had a tendency to balance with the additive concentration in the water and membrane interface, which forced the tertiary amine based amphiphilic copolymers to diffuse out of the membrane matrix and dissolve into the water environment. This migration stops when the concentration difference becomes zero [7,43]. In this study, the additive concentration in pure water was always zero during the shaking test, resulting in a continuous migration of the copolymers from membrane matrix to the surface and even into the water environment.…”
Section: Composition Stability Of Blend Membranesmentioning
confidence: 86%
“…The additive concentration in membrane matrix had a tendency to balance with the additive concentration in the water and membrane interface, which forced the tertiary amine based amphiphilic copolymers to diffuse out of the membrane matrix and dissolve into the water environment. This migration stops when the concentration difference becomes zero [7,43]. In this study, the additive concentration in pure water was always zero during the shaking test, resulting in a continuous migration of the copolymers from membrane matrix to the surface and even into the water environment.…”
Section: Composition Stability Of Blend Membranesmentioning
confidence: 86%
“…Suk et al 7 studied PES (Vicrex 4100P) modified by SMM and suggested that SMMs migrate to the surface from the cast films during evaporation. The SMMs were preferentially oriented with fluorocarbon groups at the outermost surface of the membrane, and the amount of fluorine on the surface depended on the thickness of the wet membrane.…”
Section: Introductionmentioning
confidence: 99%
“…According to literature, several techniques have been designed and employed successfully, including surface grafting polymerization induced by radicals, ultraviolet irradiation, plasma, electron-beam, γ -irradiation [2][3][4][5], preadsorption [6], and coating [7]. However, some inherent drawbacks of these methods mentioned above have been recognized, such as (a) undesired homopolymer produced along with surface grafting polymerization wastes expensive starting materials; (b) the adsorbed or coated polymers may not remain on the surface permanently due to the weak forces between the modifying polymers and the substrate; (c) many of these surface modification methods are complicated and require at least an additional step in the membrane preparation process [8].…”
Section: Introductionmentioning
confidence: 99%